Morfogênese da grama-missioneira-gigante em resposta à adubação com dejeto líquido de suínos - Zabot, Valdirene (2012)
It was evaluated the morphogenesis of giant-missionary grass was evaluated in response to pig slurry fertilization, whose rates (0, 40, 80, 120, 160 e 200 m³/ha/year) were fractioned in four applications, after the pasture cuttings. The experiment was carried out in the field and the evaluations were performed between spring and summer 2010-2011. The response to pig slurry was positive and linear for: canopy height, tiller density, length of leaf (blade+sheat)/tiller, number of senescent leaves, culm elongation, leaf elongation rate, final leaf blade length, leaf senescence rate, and pseudoculm elongation rate. The senescence elongation rate and senescent leaf length increased quadratically in function of pig slurry. No response to fertilization was verified for appearance leaf rate, phyllochron and leaf life duration